EMPLOYEE NARCISSISM AND WORKPLACE PERFORMANCE: CAN SUPERVISOR SUPPORT MITIGATE THE NEGATIVE EFFECTS? (The Research of Medical Science Review, 2025)
Employee narcissism presents a significant challenge to workplace harmony and performance. Narcissistic employees exhibit self-centered behaviors, lack empathy, and engage in power struggles, negatively impacting organizational effectiveness. This study investigates the relationship between employee narcissism and employee performance in public sector hospitals, with a focus on the moderating role of supervisor support. A survey was conducted among 250 nurses in Rawalpindi’s public healthcare sector, and data was analyzed using SPSS. Results reveal that narcissistic tendencies among employees reduce overall job performance, contributing to workplace conflicts and decreased teamwork. However, supervisor support weakens this negative relationship by fostering a structured, fair, and motivational work environment. These findings highlight the critical role of leadership in managing workplace narcissism to maintain productivity and organizational harmony.